German Origin Clusters for High Cardiovascular Risk in an Italian Enclave - Saugo, Mario; Basso, Giancarlo; Martini, Bortolo; Caffi, Sandro; Mazza, Alberto; Pessina, Achille C.; Scarpa, Roberta; Guglielmi, Francesco; Casiglia, Edoardo; Tikhonoff, Valérie (International Heart Journal, 2005)
Mortality and morbidity appear to be higher in a Cimbrian population representing an enclave of people who migrated from medieval Germany to the secluded Leogra valley in Italy. A population-based study was organized, recruiting 881 elderly subjects of Cimbrian origin and comparing them with a standard control population (SCP, n = 3282) having comparable general characteristics and lifestyle. Serum lipids and glucose, blood pressure, heart rate, respiratory function, ECG abnormalities, and historical events were used as risk indicators. Age-adjusted systolic and pulse pressure were higher in the Cimbrians than in the SCP, while diastolic blood pressure was comparable. The prevalences of arterial hypertension, isolated systolic hypertension, and pulse hypertension were significantly more represented among Cimbrians than SCP. The prevalences of diabetes, hypercholesterolemia, and hypertriglyceridemia were higher among the former than the latter. The ratio between apolipoproteins B and A1 was also higher, while the HDL fraction was significantly lower in Cimbrians than in the SCP. In Cimbrians, the relative risk (RR) for ischemic heart disease was 1.92 (1.57-2.34) in women, 2.30 (1.54-3.43) in men and 1.03 (1.00-1.06) in women for stroke, 2.43 (1.54-3.83) in men and 1.45 (1.01-1.12) in women for atrial fibrillation, 3.85 (2.83-5.24) in men and 1.39 (1.20-1.60) in women for respiratory disease, 1.97 (1.32-2.94) in men and 6.81 (4.38-10.60) in women for intermittent claudication, and 3.31 (2.44-4.50) in men and 2.30 (1.76-3.01) in women for left ventricular hypertrophy. The subjects living in the secluded Leogra valley are at higher cardiovascular risk than the standard controls. Whether this depends on genetic factors, lifestyle, or both will need to be clarified by further analysis.